German contemporary Soteriology. Subjects and authors - Justo Domínguez, Emilio J. (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
To think the salvific dimension of the Christian mystery and the fact of the salvation has been always a fundamental worry of the theology. Through the dialog with the modernity the interest on the soteriology has become greater, since in salvation’ topic meet the reflections on God, on Christ and on the human being. In this article it is presented the current soteriological reflection in area of German language. It is emphasized the configuration of the soteriology like a specific theological subject, her basic themes (Christ’ action, overcoming of the sin, reconciliation) and some significant authors.